(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2023)
The behavior of corrosion of AZ31 Mg alloy was studied in (SBF) “Simulated Body Fluid” by electrochemical analysis technique to realize the role of coating with (Ti) by DC sputtering with the absence and presence of oxygen. The coating by (Ti) with the absence of oxygen enhanced the stability of the corrosion product as MgO through decreasing the corrosion current density. While the presence of oxygen during coating accelerated the corrosion rate due to increasing the cathodic polarization through the reduction of oxygen and then increasing the dissolution of Mg from the substrate. The coating by (Ti) gave protection efficiency reach (33.742%). While the presence of oxygen during DC sputtering promotes the cathodic area on grains as ( ) leading to localizing the corrosion around the phases at the grain boundaries.